The Twenty-First Century Wars. Unconventional Conflicts Before International Law - Marsili, M. (10th Conference of the International Society of Military Science, 2020)
The lines between conventional and unconventional conflicts become blurred. Alongside non-international and international conflicts, a third category of armed conflict is emerging: hybrid, asymmetric, and transnational conflicts which involve state and non-state actors whose legal status and classification is disputed. While it’s a blend of traditional and irregular tactics, hybrid warfare makes use of a wide range of tools: military and civilian; conventional and unconventional. Hybrid warfare was linked almost exclusively with non-state actors. Afterwards the concept of hybrid warfare developed in a way that is now commonly accepted to describe the interplay between conventional and unconventional means used also by governments and regular armies. For such emerging conflicts/warfare there is no legal definition, therefore leaving room for interpretation and applicable law. International law (IL) and international humanitarian law (IHL) – in particular the law of war (Geneva and Hague law) – apply in case of armed conflict. The law of war, a branch of public international law, sets the acceptable justifications to engage in war (jus ad bellum) and the limits to acceptable wartime conduct (jus in bello). The law of war regulates inter alia: declaration of war; acceptance of surrender and the treatment of prisoners of war; military necessity, along with distinction and proportionality; and the prohibition of certain weapons that may cause unnecessary suffering.